Angiotensin Receptor Blocker and Calcium Channel Blocker Preventing Atrial Fibrillation Recurrence in Patients with Hypertension and Atrial Fibrillation: A Meta-analysis - Haotian Ma; Hongcheng Jiang; Jing Feng; Yong Gan (Cardiovascular Therapeutics, 2021)
Background. Atrial fibrillation (AF) is the most common serious cardiac rhythm disturbances and is responsible for substantial morbidity and mortality in general population. Hypertension is the most prevalent and potentially modifiable risk factor for AF. This study is aimed at evaluating the effect of angiotensin receptor blocker (ARB) or calcium channel blocker (CCB) on AF recurrence among patients with hypertension and AF. Methods. The PubMed, EMBASE, Medline, and Cochrane Collaboration of Controlled Clinical Trials registry databases were searched from their inception to September 2020. Results. A total of 7 randomized controlled trials (RCTs) enrolling 1495 patients were included in our study. This finding showed that ARB had a statistically significant superiority in preventing AF recurrence (OR: 0.43, 95% CI: 0.30-0.72, P=0.0006) and persistent AF (OR: 0.41, 95% CI: 0.24-0.71, P=0.001) compared to CCB. Subgroup analysis showed that there was a significant difference in telmisartan subgroup (OR: 0.54, 95% CI: 0.23-1.29, P=0.17) and nontelmisartan subgroup (OR: 0.42, 95% CI: 0.23-0.77, P=0.005). Subgroup analysis indicated that nifedipine subgroup did not show a statistically significant difference on AF recurrence between ARB and CCB (OR: 0.88, 95% CI: 0.46-1.68, P=0.69), but amlodipine subgroup showed that ARB had a significant superiority in prevention of AF recurrence (OR: 0.39, 95% CI: 0.27-0.56, P<0.0001) compared with CCB. Conclusions. This study suggests that ARB is superior to CCB for preventing the AF recurrence and persistent AF among patients with hypertension and AF.